Integrating habitat connectivity and fishing pressure to promote migratory marine species conservation - Guodong Li; Cuicui Feng; Haibin Han; Xinyun Ge; Rongliang Zhang; Fangping Cheng; Xin Fang; Han Dong; Chang Liu; Wei Huang; Jiangning Zeng (Reviews in Fish Biology and Fisheries, 2026)

Mechanistic Insights into LGALS3-Mediated Osteoarthritis Progression: Activation of the cGAS-STING Pathway as a Key Driver of Senescence-Related Osteoarthritis - Ruolan Wu; Tong Xiao; Zhen Chen; Qitao Yan; Ying Wang; Dingwei Peng; Jingli Chen; Ge Zeng (Journal of Pharmaceutical Innovation, 2026)

A new BCI paradigm based on biological brain – digital twin brain dialogue - Ting Zhang; Rongxin Zhang; Xin Zeng; Min Zeng; Yuanhang Xu; Yue Xiong; Ge Zhang; Daqing Guo; Dezhong Yao (Cognitive Neurodynamics, 2026)

Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Recycled seawater chlorine in the lithospheric mantle facilitates metal enrichment in collisional orogens - Jingbo Zhang; Rui Wang; Zoltán Zajacz; Alexandra Tsay; Adam C. Simon; Wen-Jie Xia; Yun-Zhao Ge; Zeng-Qian Hou (Earth and Planetary Science Letters, 2026)

CvbZIP81 contributes to selenium accumulation by regulating sulfate transports in Cardamine violifolia - Luxin Feng; Jiarui Zheng; Sirui Zeng; Ge Li; Sisi Wang; Ping Yun; Zexiong Chen; Renhua Huang; Qiangwen Chen; Sergey Shabala; Feng Xu (Plant Science, 2026)

Dual role of cold plasma in suppressing the growth, remodeling cellular ultrastructure and stimulating metabolic response of Kazachstania exigua from transcriptomic insight - Binyao Wang; Qing Du; Liangpeng Yuan; Longhua Pan; Yi Tang; Menglu Yang; Wenjian Wang; Dengshui Peng; Huajia Li; Shan Zeng; Lihong Ge; Jianping Yang; et al. (Food Research International, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

Molecular responses of dissolved organic matter to surface water–groundwater interactions in the Tibetan Plateau - Bing Yi; Shiyu Liu; Wei He; Xiaorui Chen; Xu Cao; Wei Kang; Xianjiang Zeng; Xian-ge Wang; Bing Zhou; Liang Zhu; Fei Liu (Journal of Hydrology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Structural characterization and biological activities of specialized metabolites from mangrove-derived fungi Aspergillus sp. - Jiajia Liu; Yue Zeng; Xinxu Ge; Yang Long (Phytochemistry, 2026)

Spatial heterogeneity, source apportionment and ecological risks of trace metal(loid)s in lakes across China - Xue Li; Weijie Yao; Hui Zeng; Xuan Hou; Bin Wang; Xing Yang; Chengjun Ge; Hailong Zhou; Jiwei Luo; Xueqiang Lu (Journal of Hazardous Materials, 2026)

Agricultural anthropogenic attribution of nitrate in karst river basin: Insights from nitrate dual isotopes and Bayesian mixing model - Xinyi He; Jie Zeng; Qixin Wu; Qian Zhang; Zhong-Jun Wang; Jie Ren; Qing Ma; Jie Zhang; Xin Ge (Journal of Environmental Management, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Intelligent Vessels Localization Based on Adaptive Correlation Information Filter Network in Complex Marine and Port Environments - Lei Yan; Wei Zeng; Zhixin Xia; Bo Meng; Junli Ge; Deming Kong (Journal of Marine Science and Engineering, 2026)
Accurate and robust localization is essential for intelligent vessels operating in complex marine and port environments. However, single-sensor localization is often affected by limited observation range, environmental occlusion, local interference, and sensor degradation. Although multi-sensor fusion can improve localization reliability, unknown cross-correlated measurement noise arising from shared disturbances, time synchronization errors, communication delays, and inconsistent fusion rates may degrade traditional information-filter-based fusion methods. To address this problem, this paper proposes an Adaptive Correlation Information Filter Network (ACIFNet) for multi-sensor fusion localization of intelligent vessels. ACIFNet preserves the recursive structure of the extended information filter and uses a Transformer-based network to learn adaptive information-domain fusion weights, thereby compensating for unknown inter-sensor correlations without explicitly estimating the full correlation covariance matrix. Experiments on constant-velocity, coordinated-turn (CV), and three-degree-of-freedom vessel motion models, together with a real-world restricted-waterway dataset, demonstrate that ACIFNet achieves higher localization accuracy and stability than Edge Incorporative Fusion (EIF)-inexact fusion, measurement fusion, and KalmanNet. In the CV and three-degree-of-freedom experiments, ACIFNet reduces the mean RMSE by 48.7%, 23.2%, and 26.1%, respectively, compared with KalmanNet. On the real-world dataset, ACIFNet achieves a mean position error of 9.90 m, an RMSE of 11.24 m, and a cross-track error of 8.72 m. These results show that ACIFNet effectively combines the interpretability of information filtering with the adaptive representation capability of neural networks for robust multi-sensor fusion localization under unknown cross-correlated measurement noises.

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

π-Bridge strategy in conjugated organic polymers activates charge- and energy-involved dual pathways for photocatalytic H₂O₂ production - Xin Sun; Tianyi Wang; Sharidya Rahman; Yuhui Ge; Jindi Yang; Chuanbiao Bie; Hao Zhang; Jacek J. Jasieniak; Xiwang Zhang; Thomas E. Rufford; Xiangkang Zeng (Chemical Engineering Journal, 2026)

CuFe dual single atoms synergistically modulate the reaction pathways to achieve efficient ammonia synthesis - Zhen Zeng; Mingtao Yang; Hongjin Xia; Kai Ge; Qingyang Li; Boxiong Shen; Yidong Hu (Chemical Engineering Journal, 2026)

Miniaturized mass spectrometry integrated with ambient ionization sources: a review of system-level advances and emerging analytical applications - Zhaoying Wang; Jianyu Weng; Mengyao Liu; Yiqi Xia; Wenqiang Gu; Hongping Zeng; Xiangyu Wang; Miaoxiu Ge; Wei Xiong; Luhong Wen (Analytica Chimica Acta, 2026)

α-Glucosidase inhibitory and tyrosinase inhibitory activities of alkaloids from Stephania kwangsiensis - Siwen Zeng; Jing Li; Yonglin Huang; Yafeng Wang; Bingyuan Yang; Zhangbin Liu; Guiqin Li; Li Ge; Ruijie He; Kedi Yang (Natural Product Research, 2026)

Physics-guided spatiotemporal deep learning for urban flood prediction: interpretable modelling with integrated gradients - Bowei Zeng; Jun Niu; Ge Yang; Mingyu Ouyang; Guoru Huang; Wenjie Chen; Jiaxuan Zheng (Frontiers in Marine Science, 2026)
Urban flooding is intensifying under climate change and urbanization, demanding efficient deep learning-based prediction. However, such models are commonly trained to minimize data-fitting loss alone, with limited incorporation of physical constraints on surface water flow. As a result, they may learn spurious statistical relationships and provide little insight into the factors governing predicted inundation, limiting their practical value for flood risk management. This study develops a physics-guided and interpretable deep learning framework for compound rainfall-tidal flood prediction in a representative coastal island setting, where flood dynamics are strongly shaped by interactions between rainfall forcing, terrain controls, and tidal boundary conditions. The framework integrates a U-Net encoder-decoder for spatial feature extraction, along with Bidirectional LSTM branches and multi-head self-attention, to encode rainfall and tidal time series. Physics-guided loss functions that enforce gradient consistency and spatial smoothness are introduced via staged weight scheduling to improve physical plausibility while preserving predictive accuracy. Model interpretability is further achieved using Integrated Gradients to quantify feature contributions, with robustness confirmed by K-fold stability analysis and independent ablation experiments. Results show that drainage junctions emerge as the dominant predictor under the present architecture–task setting, while terrain-related variables jointly account for the majority of attribution, indicating that the model captures key hydraulic and topographic controls on inundation. The resulting importance hierarchy, in which drainage junctions and geomorphological features jointly exceed the contribution of elevation, is preserved in a paired no-physics baseline trained under an otherwise identical configuration, with a cross-model Spearman rank correlation of ρ = 1.00 under the mean-depth target. This robustness identifies the hierarchy as a property of the architecture-task pairing rather than of the physics-guided loss terms; the latter act instead as an output-level hydraulic regulariser, reducing gradient-consistency violations by 16.7% at a marginal 0.51% reduction in R². These findings demonstrate that integrating physical constraints with gradient-based attribution analysis can yield more credible and interpretable deep learning predictions for compound urban flooding.

A Portable Smartphone-assisted Sensor for Detection of Iodate Based on Triphenylamine Oligomer - Yue Zhang; Mingyi Guan; Hui Li; Xiaoyu Zeng; Lu Yang; Xiaofang Ding; Xiaoping Fan; Daoxing Chen; Mengtuan Ge (Journal of Fluorescence, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Starch-driven lead immobilization by a new isolated phosphate-solubilizing fungus Talaromyces flavus MC-F1: A cost-effective two-step strategy - Mingchen Xia; Peng Bao; Shilong He; Weimin Zeng; Guanzhou Qiu; Mengyao Ge (Journal of Environmental Chemical Engineering, 2026)

Numerical simulation towards scaling-up industrial Gas-Solid fluidized bed for the separation of clean coal particles - Ying Jia; Mian Zeng; Yong Zhang; Xianqiang Xiong; Huihuang Xia; Enhui Zhou; Ji Xu; Chenlong Duan; Yuqing Feng; Wei Ge (Fuel, 2026)

Rapid geographical traceability and quality identification of black tea via integration of ambient mass spectrometry and machine learning - Hongping Zeng; Xiangyu Wang; Miaoxiu Ge; Mengyao Liu; Zhaoying Wang; Xiangyu Kong; Jianyu Weng; Xiaoming Du; Wei Xiong; Luhong Wen (Food Research International, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Multi-system geochronometer constraints on thermo-tectonic evolution of the Qiangtang Terrane, central Tibetan Plateau: Reply to Comment - Qingqing Lei; Xiaofan Wan; Xiang Ge; Xiaowei Zeng; Chuanbo Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of photoaged polystyrene microplastics and nanoplastics on the extracellular aggregation and intracellular accumulation of ZnO nanoparticles to algae - Qiong Zeng; Ruohua Qu; Qiong Wen; Na Liu; Fei Ge (Journal of Environmental Sciences, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Ecologically engineered seawall revetments for enhancing marine biodiversity: elevation and design options - Junbao Huang; Peng Yun; Yu Han; Qing Lyu; Huayu Chen; Zengfeng Li; Jiali Gu; Jian Zeng; Zhenming Ge (Coastal Engineering, 2026)

A Deep Reinforcement Learning Approach for Joint Resource Allocation in Time-Varying Underwater Acoustic Cooperative Networks - Liangliang Zeng; Tongxing Zheng; Yifan Wu; Yimeng Ge; Jiahao Gao (Journal of Marine Science and Engineering, 2026)
Underwater acoustic sensor networks (UASNs) have emerged as a pivotal technology for ocean exploration, tactical surveillance, and environmental monitoring. However, the underwater acoustic channel poses severe challenges, including high propagation delay, limited bandwidth, and rapid time-varying multipath fading, which significantly degrade communication reliability. Cooperative communication, which exploits spatial diversity via relay nodes, offers a promising solution to these impairments. In this paper, we investigate the joint optimization of relay selection and power allocation in UASNs to maximize the long-term system energy efficiency and throughput. This problem is inherently complex due to the hybrid action space, which couples the discrete selection of relay nodes with the continuous allocation of transmission power, and the absence of real-time, perfect channel state information (CSI). To address these challenges, we propose a novel deep hybrid reinforcement learning (DHRL) framework utilizing a parameterized deep Q-Network (P-DQN) architecture. Unlike traditional approaches that discretize power levels or relax discrete constraints, our approach seamlessly integrates a deterministic policy network for continuous power control and a value-based network for discrete relay evaluation. Furthermore, we incorporate a prioritized experience replay (PER) mechanism to improve sample efficiency by focusing on rare but significant channel transition events. We provide a comprehensive theoretical analysis of the algorithm’s complexity and convergence properties. Extensive simulation results demonstrate that the proposed DHRL algorithm outperforms state-of-the-art combinatorial bandit algorithms and conventional deep reinforcement learning baselines in terms of system energy efficiency, and also exhibits superior robustness against channel estimation errors.

Additive manufacturing of silicon nitride ceramics via DLP: A synergistic engineering strategy for achieving ultra-high solid loading slurries - Qing Qin; Zihan Guo; Runze Liu; Siran Yin; Gang Xiong; Zhen Shen; Xiaojun Zeng; Changchun Ge (Chemical Engineering Journal, 2026)

Metagenomic insights into species shifts and adaptation mechanisms of anammox communities treating incineration leachate - Da Kang; Yikai Zhao; Xinran Zhang; Xianyong Zeng; Xindi Fu; Bingxin Li; Zheng Ge; Liang Zhang; James P. Shapleigh; Yongzhen Peng (Chemical Engineering Journal, 2026)

Decoding Plant Growth-Promoting Rhizobacteria Volatile Organic Compounds Mediated Growth Promotion in Malus domestica - Nan Zeng; Dandan Wang; Jiahe Pang; Xin Yu Zhao; Chunji Li; Dingcun Zhang; Junliang Ge; Die Zhao; Rutao Gai; Ziqi Cao; Xinyue Bi; Ning Zhang; et al. (Journal of Plant Growth Regulation, 2026)

PROSAIL-DNN: a fine-tuning transfer learning framework for field-scale oat leaf area index monitoring from UAV imagery - Pengpeng Zhang; Bing Lu; Jiali Shang; Shuaijie Shen; Junyong Ge; Xingyu Wang; Shuchang Sun; Yadong Yang; Huadong Zang; Zhaohai Zeng (Computers and Electronics in Agriculture, 2026)

Non-antibiotic drug berberine boosts the spread of high-risk antibiotic resistance genes in aquaculture through gut microbiota and function shifts - Wei Li; Jieyi Zeng; Ningguo Zheng; Chaorong Ge; Yaying Li; Xinli An; Huaiying Yao (Aquaculture, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Atmospheric wet deposition of silicon in coastal urban area, Southeast China: Variations, determinants, sources, and potential environmental effects - Kunxiang Wang; Jie Zeng; Xiaomin Yang; Qixin Wu; Qing Ma; Shijun Mao; Zixuan Liu; Jingwen Chen; Zhong-Jun Wang; Xin Ge (Urban Climate, 2026)

Multi-system geochronometer constraints on thermo-tectonic evolution of the Qiangtang Terrane, central Tibetan Plateau - Qingqing Lei; Xiaofan Wan; Xiang Ge; Xiaowei Zeng; Chuanbo Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Ultra-stable self-supported bifunctional iron phosphide catalysts for anion exchange membrane water electrolyzer at industrial-scale current density - Siyi Liu; Xingbo Ge; Chao Lv; Ning Zeng; Zezheng Zhang; Qin Li; Jinguang Cai (Chemical Engineering Journal, 2026)

Multifunctional nanocellulose enables robust UV resistance, hydrophobicity and antibacterial activity of polyamide 612 composites - Chenyang Wang; Hou-Yong Yu; Somia Yassin Hussain Abdalkarim; Meijin Jin; Xiaohua Wang; Zengwen Yao; Dengteng Ge; Cheng Zeng; Shengjian Wang; Haojie Zang (Chemical Engineering Journal, 2026)

Zn2+-DTPMPA chelated cellulose nanocrystal hybrid: synergistic flame-retardant, antibacterial and mechanical reinforcement mechanisms for PA66 composites - Gang Long; Xue Ma; HouYong Yu; Meijin Jin; Xuefei Chen; Xiaohua Wang; Zengwen Yao; Dengteng Ge; Cheng Zeng; Shengjian Wang; Haojie Zang; Yi Jiang (Carbohydrate Polymers, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Dynamic characteristics analysis of pneumatic collection device for continuous harvesting of dry safflower based on CFD-DEM - Chao Sun; He Zhang; Yun Ge; Haifeng Zeng; Yijiang Zheng (Computers and Electronics in Agriculture, 2026)

A network-based framework for cost-effective Green–Grey retrofitting of urban drainage systems - Ge Yang; Bowei Zeng; Wenjie Chen; Guoru Huang (Sustainable Cities and Society, 2026)

Effects of seawall revetment surface modifications on marine biodiversity: A case study in China - Peng Yun; Junbao Huang; Qing Lyu; Huayu Chen; Jiali Gu; Jian Zeng; Zhenming Ge (Regional Studies in Marine Science, 2026)

Refining the regionalization for debris flows along the eastern margin of the Qinghai-Tibet Plateau - Xinyue Liang; Yonggang Ge; Lu Zeng; Yuqing Sun; Liqun Lyu (CATENA, 2026)

Porcine reproductive and respiratory syndrome virus downregulates the circ-107191/miR-34c/RAD54L axis to promote testicular cell apoptosis via impaired homologous recombination repair - Bingzhou Huang; Dong You; Baoling Liu; Siyuan Lai; Yanru Ai; Jianbo Huang; Yuancheng Zhou; Liangpeng Ge; Xiu Zeng; Zhiwen Xu; Ling Zhu (Theriogenology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Rainfall process-related dissolved organic carbon wet deposition at the southern foot of Qinling Mountain: Implications for atmospheric carbon budget at the boundary area between north and south China - Jie Zeng; Guilin Han; Qixin Wu; Lihong Fu; Qing Ma; Jie Zhang; Xinyi He; Xin Ge (Journal of Hydrology, 2025)

Conventional microplastics pose higher short-term risks to crop growth than biodegradable alternatives: Evidences from a two-year field trial - Yan Liu; Juncong Chu; Lang Cheng; Zhengjun Yan; Yue Wang; Junyong Ge; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Cleaner Production, 2025)

Interaction mechanism of cellulose pyrolysis over alumina-coupled Ce-Zr catalysts for aldehyde–ketone compounds - Shuanghui Liu; Zefeng Ge; Mingxun Zeng; Huiyan Zhang (Chemical Engineering Journal, 2025)

An interface-engineered three-channel synapse using staggered transition metal dichalcogenides/ferroelectric heterojunctions - Yuqing Zhou; Qibin Zeng; Xingke Fu; Chao Yang; Feiyan Hou; Chen Ge; Kaiyang Zeng; Huajun Liu; Zheng Chai; Tai Min; Tao Li (Chemical Engineering Journal, 2025)

Structure characterization and anti-infection activity of a homogeneous heteropolysaccharide COP-60a from Cornus officinalis leaf - Yi Xiong; Wenchen Yu; Ge Wang; Deyong Zeng; Xiaoyi Li; Jingxuan Jia; Jianlong Wang; Yue Zhang; Jianguo Guo; Yingyu Zhou; Weihong Lu (Carbohydrate Polymers, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Atmospheric occurrence and gas-particle partitioning of cholesteric liquid crystal monomers: Another significant class of persistent and mobile e-waste pollutants of emerging concern - Weisheng Luo; Xiang Ge; Jiali Ge; Benyu He; Bibai Du; Huan Yi; Yanlan Zhao; Lixi Zeng (Journal of Hazardous Materials, 2025)

Spatiotemporal correlations of water network elements in Yilong Lake Basin and the drivers—an analysis based on the PLS-DSDM model - Yunan Huang; Xuesen Zhang; Yunchun Chen; Zuokai Xie; Xiaofei Guo; Jiansheng Zhang; Lijun Liao; Xingyan Ge; Xingpeng Liu; Weijun Zeng (Environmental Research, 2025)

Amino acid functionalized carbon sheet network with confinement effect for capacitive desalination and supercapacitor - Chengyan Ge; Jing Huang; Jiani Wang; Yini Song; Jianping Zeng; Dawei Wang; Yujing Zheng; Guiyun Yu; Yong Dai; Yue Lian (Desalination, 2025)

Boosting photochromism and room-temperature-phosphorescence for multi-dimensional dynamic encryption via donor–acceptor anion–π interaction - Yang Hua; Jian-Ge Zeng; Chun-Jie Liu; Ming-Sheng Wang; Li Li (Chemical Engineering Journal, 2025)

Gold nanoclusters as multifunctional nanoantibiotics: synthesis, mechanisms and applications in combating bacterial infections - Baiyang Liu; Zheming Yang; Jinwen Zhou; Bingbing Chen; Wenjia Li; Jing Hou; Xinmiao Wang; Shipeng Ning; Ge Xu; Xinhui Zeng; Qing Li; Zengchao Guo; et al. (Chemical Engineering Journal, 2025)

Risk and driving factors of nitrogen and phosphorus runoff losses under extreme rainfall conditions: sludge application strategies in forest soils - Yuantong Yang; Xiaojun Ge; Weixun Feng; Lihua Xian; Guodong Shao; Jianbo Liao; Shucai Zeng (CATENA, 2025)

Nitrogen-containing pollutant records in rainfall from the north-south boundary area in China: Compositions, variations, and sources - Xinyi He; Jie Zeng; Qixin Wu; Qing Ma; Jie Zhang; Lihong Fu; Xin Ge (Process Safety and Environmental Protection, 2025)

Occurrence, removal and ecotoxicological assessment of halogenated dissolved organic matter in waste leachates - Xian-Ge Wang; Wei He; Xiao-Song He; Xu Cao; Yue Sun; Xian-Jiang Zeng (Journal of Hazardous Materials, 2025)

Dual inhibition of As(III) mobilization and greenhouse gas emission achieved by photocatalytic birnessite-nitrate amendments in flooded paddy soils - Zheng Chen; Xiyu Zhao; Shutong Zeng; Honghui Wang; Liyun Ge; Jing Zhang; Yixin Wu; Shuyun Zhang; Ruotong Mao; Hui Gao; Siwen Xia (Journal of Environmental Chemical Engineering, 2025)

The adaptability of vegetation productivity to precipitation variability determines its resistance in central asian grassland ecosystems - Na Zeng; Xiaoli Ren; Zhongen Niu; Rong Ge (Journal of Arid Environments, 2025)

Rainfall-driven heavy metals wet deposition in a typical small city at southern foothills of Qinling Mountains, the boundary zone of north and south China - Jie Zhang; Jie Zeng; Qixin Wu; Xin Ge; Xinyi He; Lihong Fu (Environmental Pollution, 2025)

A magnetically levitated platform with multi-directional quasi-zero stiffness for low-frequency vibration protection - Wenhao Qi; Tianyu Zhao; Qiuhua Gao; Jiajia Lu; Fanchi Zeng; Ge Yan; Wenming Zhang (Engineering Structures, 2025)

Biogeomorphology and carbon sequestration in a coastal shoal invaded by Spartina alterniflora in the Yangtze Estuary: 22-year simulation for management implication - Ke-Hua Zhu; Zhen-Ming Ge; Ying Huang; Lei-Hua Zhao; Zeng-Feng Li; Wei Zhao; Hua-Yu Chen; Dan Zhang; Hai-Feng Cheng; Wei Zhang; Pei Xin (Ecological Engineering, 2025)

A novel non-nad-based PARP1 inhibitor, Japoflavone B, triggered Caspase-3/GSDME-mediated pyroptosis through ROS/p38/p53 pathway in NSCLC - Haoqiang Wan; Jipeng Wei; Yang Wang; Lanlan Ge; Qiaoqiao Hu; Yangfang Li; Boping Zhou; Xiaobin Zeng (Chemico-Biological Interactions, 2025)

Association Between Folate Metabolism Risk, Collateral Circulation, and Hemorrhagic Risk in Moyamoya Disease - Junsheng Li; Qiheng He; Chenglong Liu; Chaofan Zeng; Zhiyao Zheng; Bojian Zhang; Siqi Mou; Wei Liu; Wei Sun; Peicong Ge; Dong Zhang; Jizong Zhao (Translational Stroke Research, 2025)

Neural Responses to Hypoxic Injury in a Vascularized Cerebral Organoid Model - Yang Li; Xin-Yao Sun; Peng-Ming Zeng; Zhen-Ge Luo (Neuroscience Bulletin, 2025)
Hypoxic injury (HI) in the prenatal period often causes neonatal neurological disabilities. Due to the difficulty in obtaining clinical samples, the molecular and cellular mechanisms remain unclear. Here we use vascularized cerebral organoids to investigate the hypoxic injury phenotype and explore the intercellular interactions between vascular and neural tissues under hypoxic conditions. Our results indicate that fused vascularized cerebral organoids exhibit broader hypoxic responses and larger decreases in panels of neural development-related genes when exposed to low oxygen levels compared to single cerebral organoids. Interestingly, vessels also exhibit neural protective effects on T-box brain protein 2 + intermediate progenitors (IPs), which are markedly lost in HI cerebral organoids. Furthermore, we identify the role of bone morphogenic protein signaling in protecting IPs. Thus, this study has established an in vitro organoid system that can be used to study the contribution of vessels to brain injury under hypoxic conditions and provides a strategy for the identification of intervention targets.

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Unveiling the urban rainfall chemistry in summer frequent-rainy area: Variation and source identification of air pollutants based on two rainy seasons’ observation - Shijun Mao; Zixuan Liu; Jie Zeng; Qixin Wu; Xin Ge (Journal of Environmental Management, 2025)

Simultaneous determination of pesticide residues and rapid discrimination of corn production origin using ambient ionization mass spectrometry combined with machine learning - Hang Su; Lifeng Han; Miaoxiu Ge; Xiangyu Wang; Hongping Zeng; Dan Zhao; Wei Xiong; Luhong Wen (Food Chemistry, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Biofilm-overproducing Bacillus amyloliquefaciens strain B9ΔywcC reduces cadmium uptake in lettuce by upregulating the expression of proteins associated with root surface biofilm formation and cell membrane homeostasis - Lijing Sun; Rongrong Gao; Qian Zeng; Zhanbiao Ge; Xiafang Sheng; Linyan He (Journal of Hazardous Materials, 2025)

Astragalus polysaccharide slows the dissemination of antibiotic resistance genes and reduces the prevalence of opportunistic pathogens in the fish gut - Wei Li; Jieyi Zeng; Ningguo Zheng; Chaorong Ge; Yaying Li; Xinli An; Huaiying Yao (Journal of Environmental Management, 2025)

Comprehensive review of ecological risks and toxicity mechanisms of microplastics in freshwater: Focus on zebrafish as a model organism - Haichao Sha; Xi Li; Qi Li; Jingwei Zhang; Ji Gao; Lukun Ge; Weinan Wang; Taotao Zeng (Aquatic Toxicology, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

Bromine radicals and hydroxyl radicals efficiently degrade emerging organic contaminants in the UVA photolysis of bromine process - Tao Yang; Xiujuan Kong; Ge Zeng; Maoju Jiang; Linqian An; Peng Su; Qixiao Lv; Jun Ma; Juan Li (Journal of Environmental Chemical Engineering, 2025)

TKSF-KAN: Transformer-enhanced oat yield modeling and transferability across major oat-producing regions in China using UAV multisource data - Pengpeng Zhang; Bing Lu; Jiali Shang; Changwei Tan; Qihan Xu; Lei Shi; Shujian Jin; Xingyu Wang; Yunfei Jiang; Yadong Yang; Huadong Zang; Junyong Ge; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Visible light can also efficiently activate chlorine dioxide for the abatement of micropollutants - Bin Zhang; Zhiyun Long; Ge Zeng; Wenjun Zhang; Peng Su; Xiangyang Hou; Qixiao Lv; Wenqi Li; Jin Jiang; Zihao Wu; Tao Yang (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Using explainable machine learning to predict the irritation and corrosivity of chemicals on eyes and skin - Yingxu Liu; Yang Liu; Simeng Zhang; Chen Zeng; Qing Zhang; Yunya Jiang; Xi Yang; Lidan Zheng; Qian Ge; Yanmin Zhang; Yadong Chen; Mengyi Lu; et al. (Toxicology Letters, 2025)

Functional lipid diversity and novel oxylipin identification for interspecies differentiation and nutritional assessment of commercial seahorse (Hippocampus) using untargeted and targeted lipidomics - Lijun Ge; Weibo Lu; Huixiang Wu; Jingjing Liang; Jie Liao; Keyun Cheng; Xi-xi Zeng; Si-wei Wang; Zejun Wang; Peiqing Mao; Zhujun Mao; Jing Xue; et al. (Food Chemistry, 2025)

Synthesis and antiproliferative activity of CBD aromatic ester derivatives - Kang Li; Xiaomei Ge; Xinye Lv; Lei Huang; Jianguo Zeng; Pi Cheng (Natural Product Research, 2025)

Modeling diabetic cardiomyopathy using human cardiac organoids: Effects of high glucose and lipid conditions - Xiangyu Wang; Xin Tan; Ting Zhang; Shuai Xu; Yiyao Zeng; Anchen Xu; Xian Li; Ge Zhang; Yufeng Jiang; Hezi Jiang; Jili Fan; Xiaohong Bo; et al. (Chemico-Biological Interactions, 2025)

Seasonal variations in the transpiration-to-evapotranspiration ratio and their driving forces in China’s terrestrial ecosystem during 1981–2021 - Bin Wang; Zhongen Niu; Lili Feng; Na Zeng; Rong Ge; Jiayi Fan (Journal of Geographical Sciences, 2025)

Full-Scale Numerical Simulation of a Free-Running Cruise Ship in Heavy Head Sea Conditions - Shenwei Ge; Ji Zeng; Kewei Song; Junrui Jia (Journal of Marine Science and Engineering, 2025)
For a cruise ship in heavy sea conditions, self-propulsion performance prediction is important for ensuring its safety. In this study, a numerical simulation approach that models the free running of a ship is presented, and a full-scale small cruise ship is verified using a ship model experiment. Based on this method, a free-running cruise ship encountering six kinds of wave conditions was simulated, and the characteristics of the ship’s motion, added resistance, and propeller loading were analyzed. The results demonstrated that the free-running approach can simulate the self-propelled motion of a full-scale ship, and that it converges more quickly than the traditional self-propulsion simulation method. The ship’s speed, heave, pitch, and thrust fluctuated when it moved through the waves, and λ/Lwl had a greater influence on the amplitude of these fluctuations than did H/Lwl. Furthermore, the propeller loading exhibited a sharp increase, and the maximum loading coefficient exceeded 500%, which may pose a safety risk.

Accelerated retinal ageing and multimorbidity in middle-aged and older adults - Ruiye Chen; Xiaomin Zeng; Wenyi Hu; Deepak Jeyarajan; Zhen Yu; Wei Wang; Zongyuan Ge; Xianwen Shang; Mingguang He; Zhuoting Zhu (GeroScience, 2025)
The aim of this study is to investigate the association between retinal age gap and multimorbidity. Retinal age gap was calculated based on a previously developed deep learning model for 45,436 participants. The number of age-related conditions reported at baseline was summed and categorized as zero, one, or at least two conditions at baseline (multimorbidity). Incident multimorbidity was defined as having two or more age-related diseases onset during the follow-up period. Linear regressions were fit to examine the associations of disease numbers at baseline with retinal age gaps. Cox proportional hazard regression models were used to examine associations of retinal age gaps with the incidence of multimorbidity. In the fully adjusted model, those with multimorbidity and one disease both showed significant increases in retinal age gaps at baseline compared to participants with zero disease number ( β = 0.254, 95% CI 0.154, 0.354; P < 0.001; β = 0.203, 95% CI 0.116, 0.291; P < 0.001; respectively). After a median follow-up period of 11.38 (IQR, 11.26–11.53; range, 0.02–11.81) years, a total of 3607 (17.29%) participants had incident multimorbidity. Each 5-year increase in retinal age gap at baseline was independently associated with an 8% increase in the risk of multimorbidity (HR = 1.08, 95% CI 1.02, 1.14, P = 0.008). Our study demonstrated that an increase of retinal age gap was independently associated with a greater risk of incident multimorbidity. By recognizing deviations from normal aging, we can identify individuals at higher risk of developing multimorbidity. This early identification facilitates patients’ self-management and personalized interventions before disease onset.

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Roles of ecological and hydrological processes in the variability of carbon fluxes in a salt marsh of the Yangtze Estuary: Model simulations vs. measurements - Ke-Hua Zhu; Zeng-Feng Li; Wei Zhao; Li-Ming Xue; Hua-Yu Chen; Qing Lyu; Shi-Xian Liu; Zhen-Ming Ge (Agricultural and Forest Meteorology, 2025)

Towards a safer food chain: Recent advances in multi-technology based lipidomics application to food quality and safety - Jing Xue; Huixiang Wu; Lijun Ge; Weibo Lu; Honghai Wang; Peiqin Mao; Jie Liao; Xixi Zeng; Siwei Wang; Lili Jiang; Jingjing Liang; Jianying Huang; et al. (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Dynamics of biogeomorphology and CO2 sequestration in Jiangsu’s coastal salt marshes in East China following Spartina alterniflora invasion during 2011 2022 - Zeng-Feng Li; Ke-Hua Zhu; Wei Zhao; Hua-Yu Chen; Zeng Zhou; Zhen-Ming Ge (Regional Studies in Marine Science, 2025)

Dual targeting of FR+CD44 overexpressing tumors by self-assembled nanoparticles quantitatively conjugating folic acid-hyaluronic acid to the GSH-sensitively modified podophyllotoxin - Chaozheng Zhang; Yao Chen; Yi Zuo; Maolin Wang; Hongyu Chen; Chuanqi Wang; Yuening Cao; Yingjie Zeng; Ying Chen; Tingting Zhang; Xian Ge; Xiujun Cao; et al. (Chemical Engineering Journal, 2025)

Assessing carbon storage in Xinjiang’s arid grassland Ecosystems: Insights from Process-Based modeling - Haiyan Han; Jianli Ding; Jinjie Wang; Annan Zeng; Xiangyu Ge; Xiaowen Zhu (CATENA, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Comprehensive Analysis and In Vitro Verification of Endothelial-Mesenchymal Transition-Related Genes in Moyamoya Disease - Junsheng Li; Qiheng He; Zhiyao Zheng; Chenglong Liu; Bojian Zhang; Siqi Mou; Chaofan Zeng; Wei Sun; Wei Liu; Peicong Ge; Dong Zhang; Jizong Zhao (Molecular Neurobiology, 2025)

Impacts of Spartina alterniflora invasion on soil carbon components of particulate and mineral-associated organic matter and soil organic matter mineralization in estuarine wetlands - Lin Wang; Yuan Li; Jie Hei; Weiqi Wang; Jordi Sardans; Zhihao Zhang; Fanjiang Zeng; Maoquan Ge; Yiyang Liao; Yunying Fang; Tony Vancov; Jiawei Gan; et al. (Applied Soil Ecology, 2025)

Functional diversity explores the maintenance mechanism and driving factors of the invasion equilibrium state of the icefish ( Neosalanx taihuensis Chen) in Lake Fuxian, China - You Ge; Xiaohong Gu; Qingfei Zeng; Zhigang Mao; Huihui Chen; Huiting Yang; Wenlei Luo (Journal of Fish Biology, 2025)
Biodiversity loss caused by biological invasions is an ecological problem on a global scale, and understanding the mechanism of biological invasion is the basis for managing non‐native species. The biotic resistance hypothesis proposes that species‐rich native communities are less susceptible to invasion because of the limited resources available to non‐native species, therefore comparing the resource utilization patterns of different communities can reveal the invasion mechanisms of specific non‐native species at the community level. We selected Lake Taihu, where icefish ( Neosalanx taihuensis Chen) originated, and Lake Fuxian, where icefish invaded, as the research objects. We calculated the fish functional diversity indexes, including functional richness (FRic), functional evenness (FEve), and functional divergence (FDiv), to reflect differences in ecological niche and resource utilization based on four quarterly fish survey data from two lakes. The random forests model explored the relationship between functional diversity indexes and biotic and environmental variables. Our results showed that more diverse resource utilization (high FRic), more niche space (low FEve), and less competitive pressure (high FDiv) in Lake Fuxian were identified as the critical important factors for maintaining the current equilibrium state after successful invasion of icefish. The bottom‐up effects mainly affected the functional diversity indexes in Lake Fuxian. They differed from those in Lake Taihu and were primarily influenced by top‐down effects. Enhancing the top‐down effects in Lake Fuxian and limiting the zooplankton available to icefish are critical to controlling the invasion of icefish. This study offers a new perspective for studying the non‐native fish invasion mechanism, and provides scientific guidance for managing non‐native fish in Lake Fuxian.

Sulfation of hyperbranched β-glucan from mushroom Pleurotus tuber-regium enhances α-glucosidase inhibition and anti-glycation properties - Lei Chen; Peipei Ge; Tong Zeng; Lanlan Zhao; Ka-Hing Wong; Guiyang Shi; Peter C.K. Cheung; Zhongyang Ding (Food Bioscience, 2025)

Using UAV-based multispectral and RGB imagery to monitor above-ground biomass of oat-based diversified cropping - Pengpeng Zhang; Bing Lu; Junyong Ge; Xingyu Wang; Yadong Yang; Jiali Shang; Zhu La; Huadong Zang; Zhaohai Zeng (European Journal of Agronomy, 2025)

Fertilizer reduction and biochar amendment promote soil mineral-associated organic carbon, bacterial activity, and enzyme activity in a jasmine garden in southeast China - Fajun Yang; Weiqi Wang; Ziwei Wu; Jiahao Peng; Hongda Xu; Maoquan Ge; Shaoying Lin; Yu Zeng; Jordi Sardans; Chun Wang; Josep Peñuelas (Science of The Total Environment, 2024)

Arsenic mobilization and nitrous oxide emission modulation by different nitrogen management strategies in a flooded ammonia-enriched paddy soil - Feng WANG; Jing ZHANG; Yanqiong ZENG; Honghui WANG; Xiyu ZHAO; Yilin CHEN; Huanhuan DENG; Liyun GE; Randy A. DAHLGREN; Hui GAO; Zheng CHEN (Pedosphere, 2024)

Impacts of plastic pollution on soil–plant properties and greenhouse gas emissions in wetlands: A meta-analysis - Wei Zhao; Zhen-Ming Ge; Ke-Hua Zhu; Qing Lyu; Shi-Xian Liu; Hua-Yu Chen; Zeng-Feng Li (Journal of Hazardous Materials, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Comparative evaluating laser ionization and iKnife coupled with rapid evaporative ionization mass spectrometry and machine learning for geographical authentication of Larimichthys crocea - Weibo Lu; Honghai Wang; Lijun Ge; Siwei Wang; Xixi Zeng; Zhujun Mao; Pingya Wang; Jingjing Liang; Jing Xue; Yiwei Cui; Qiaoling Zhao; Keyun Cheng; et al. (Food Chemistry, 2024)

Spatiotemporal analysis of the food-related carbon emissions of China: Regional heterogeneity and the urban‒rural divide - Jinyu Han; Jiansheng Qu; Tek Narayan Maraseni; Jingjing Zeng; Dai Wang; Yujie Ge; Dingye Wu (Journal of Environmental Management, 2024)

Fusion property prediction and mineral reaction mechanism of coal/biomass ash blends upon in-situ tests in the gasification process - Zefeng Ge; Yuqing Wu; Zenghui Hou; Lijuan Sun; Mingxun Zeng; Yuna Ma; Zhenting Zha; Qiuxiang Lu; Huiyan Zhang (Fuel, 2024)

Oat/soybean strip intercropping benefits crop yield and stability in semi-arid regions: A multi-site and multi-year assessment - Wenhao Feng; Junyong Ge; Antonio Rafael Sánchez Rodríguez; Baoping Zhao; Xingyu Wang; Leanne Peixoto; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2024)

C C rupture in key monosaccharides and succedent redox in supercritical ethanol - Qianxin Sun; Chenyu Ge; Shanshan Feng; Qiufu Zeng; Guiying Li; Changwei Hu (Chemical Engineering Journal, 2024)

Regenerated spent LiFePO4 with tailored residual copper-atoms towards improved energy-storage capacity and reversibility - Zihao Zeng; Hai Lei; Jiexiang Li; Bing Wang; Shuya Lei; Xiaobo Ji; Wei Sun; Yue Yang; Peng Ge (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Unraveling the role of Mn(V)/Mn(III) in the enhanced permanganate oxidation under Vis-LED radiation - Jiamin Mai; Ge Zeng; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Xiangyang Hou; Minchao Liu; Jun Ma; Tao Yang (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Matching periodate peak absorbance by far UVC at 222 nm promotes the degradation of micropollutants and energy efficiency - Tao Yang; Ge Zeng; Maoju Jiang; Peng Su; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Juan Li (Journal of Hazardous Materials, 2024)

Harmful planktonic Microcystis and benthic Oscillatoria-induced toxicological effects on the Asian clam (Corbicula fluminea): A survey on histopathology, behavior, oxidative stress, apoptosis and inflammation - Huiting Yang; Xiaohong Gu; Huihui Chen; Qingfei Zeng; Zhigang Mao; You Ge; Yujia Yao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Evaluation of fengyun geosynchronous orbit and GPM satellites precipitation products over the southeastern Tibetan plateau - Yunfan Song; Tao Du; Bo Zeng; Qing Wu; Ge Wang (International Journal of Remote Sensing, 2024)

Complete genome sequence of a novel Pseudomonas sp. IT1137 isolated from Antarctic intertidal sediment showing potential for alkane degradation at low temperatures - Hui-Yan Ge; Yi-He Zhang; Yong-Qiang Hu; Wei Han; Yu Du; Ting Hu; Yin-Xin Zeng (Marine Genomics, 2024)

Polyvinyl chloride microplastics in the aquatic environment enrich potential pathogenic bacteria and spread antibiotic resistance genes in the fish gut - Wei Li; Jieyi Zeng; Ningguo Zheng; Chaorong Ge; Yaying Li; Huaiying Yao (Journal of Hazardous Materials, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Novel sunlight-induced monochloramine activation system for efficient microcontaminant abatement - Haochen Zhang; Maoju Jiang; Peng Su; Qixiao Lv; Ge Zeng; Linqian An; Jun Ma; Tao Yang (Water Research, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

A model coupling ecological and hydrodynamic processes for simulating the biogeomorphology of a coastal salt marsh - Ke-Hua Zhu; Jian Zeng; Zhen-Ming Ge; Yin Zuo; Shi-Hua Li; Lei-Hua Zhao; Yu Han; Hai-Feng Cheng; Pei Xin (Ecological Modelling, 2024)

For regenerated graphite: Tailoring sub-surface architecture with strong pre-storage abilities towards high-rate properties - Zhengqiao Yuan; Yu Dong; Zihao Zeng; Wenqing Zhao; Bin Wang; Hai Lei; Wei Sun; Xiaobo Ji; Yue Yang; Peng Ge (Chemical Engineering Journal, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

Wogonin alleviates sepsis-induced acute lung injury by modulating macrophage polarization through the SIRT1-FOXO1 pathways - Jinlin Ge; Huanhuan Yang; Ningning Yu; Shengle Lin; Yufeng Zeng (Tissue and Cell, 2024)

Refinement of kinetic model and understanding the role of dichloride radical (Cl2•−) in radical transformation in the UV/NH2Cl process - Haochen Zhang; Maoju Jiang; Peng Su; Qixiao Lv; Ge Zeng; Linqian An; Jiachun Cao; Yang Zhou; Shane Allen Snyder; Jun Ma; Tao Yang (Water Research, 2024)

Evolution and determinants of precipitation chemistry in a plateau city, China: Insight from the pollutants source identification and environmental effect - Jie Zeng; Guilin Han; Qixin Wu; Qing Ma; Shijun Mao; Xin Ge; Zhong-Jun Wang; Chao Yang (Urban Climate, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Analysis of the trigger conditions and activity trend in debris flow along Sichuan-Tibet traffic corridor (Xinduqiao-Changdu section) under environmental changes - Yuqing Sun; Yonggang Ge; Xingzhang Chen; Lu Zeng; Qin Tang; Xinyue Liang; Lianbin Yang (Bulletin of Engineering Geology and the Environment, 2024)

A fascinating finding: The application of traditional Chinese medicine in aquaculture prevents the spread and diffusion of antibiotic resistance genes among gut microbes - Wei Li; Jieyi Zeng; Yaying Li; Chaorong Ge; Jianqiang Su; Huaiying Yao (Aquaculture, 2024)

The promoting effect of electron beam irradiation on enzymatic saccharification and alcohol fermentation of sorghum meal: Related mechanisms - Mengting Yan; Chenyang Sun; Jiangtao Yu; Junqing Bai; Huishan Shen; Xiuyun Zhang; Yifan Lu; Zhuangzhuang Sun; Xiangzhen Ge; Wei Liang; Jie Zeng; Haiyan Gao; et al. (Journal of Cereal Science, 2024)

Investigating the influence of CaCl2 induced surface gelatinization of red adzuki bean starch on its citric acid esterification modification: Structure–property related mechanism - Wei Liang; Qian Zhang; Shuangfeng Guo; Xiangzhen Ge; Huishan Shen; Jie Zeng; Haiyan Gao; Wenhao Li (Food Chemistry, 2024)

Reactivity and kinetics of biomass pyrolysis products for in-situ reduction of NOx in a bubbling fluidized bed - Zhenting Zha; Fangzhou Li; Zefeng Ge; Qiuxiang Lu; Yuna Ma; Mingxun Zeng; Yuqing Wu; Zenghui Hou; Huiyan Zhang (Chemical Engineering Journal, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

Formation processes of groundwater in a non-ferrous metal mining city of China: Insights from hydrochemical and strontium isotope analyses - Aoshuang Mei; Xiong Wu; Yifan Zeng; Ge Zhu; Di Zhao; Yuzhe Zhang (Environmental Science and Pollution Research, 2024)

Chemical evolution of rainfall in China's first eco-civilization demonstration city: Implication for the provenance identification of pollutants and rainwater acid neutralization - Jie Zeng; Guilin Han; Qixin Wu; Meixue Peng; Xin Ge; Shijun Mao; Zhong-Jun Wang; Qing Ma (Science of The Total Environment, 2024)

Uptake, accumulation and toxicity of short chain chlorinated paraffins to wheat (Triticum aestivum L.) - Jianzhong Yu; Qing Tang; Ge Yin; Weifang Chen; Jitao Lv; Lingxiangyu Li; Chenghao Zhang; Yunxiang Ye; Xijiao Song; Xueping Zhao; Tao Tang; Changpeng Zhang; et al. (Journal of Hazardous Materials, 2024)

The role of abiotic and biotic factors of aged brine in directing microbial assembly and volatile profiles of Paocai during fermentation - Nan Zhao; Yuli Huang; Haimei Lai; Yali Wang; Yuan Mei; Xueqing Zeng; Menglu Yang; Jichun Zhao; Huajia Li; Yongqing Zhu; Renyou Gan; Lihong Ge (Food Bioscience, 2024)

Char-based Fe-Ni-Ca material for capturing AAEM from biomass pyrolysis volatiles and recyclability in catalytic reforming of volatiles - Qiuxiang Lu; Kai Wu; Zhenting Zha; Yuna Ma; Zefeng Ge; Mingxun Zeng; Shenfu Yuan; Huiyan Zhang (Chemical Engineering Journal, 2024)

A Three-Dimensional DEM Method for Trajectory Simulations of Rockfall under Irregular-Shaped Slope Surface and Rock Blocks - Liang Chen; Weiqian Zeng; Xianbiao Wang; Yang Ye; Yunfeng Ge; Dongming Gu; Shan Dong (Journal of Earth Science, 2024)

Determination of N-nitroso folic acid in folic acid and multivitamin supplements by LC-MS/MS - Yun Zeng; Jessie Teo; Jing-Quan Lim; Wei-Kiat Hoi; Chee-Leong Kee; Min-Yong Low; Xiaowei Ge (Food Additives & Contaminants: Part A, 2024)

Bacteriophages: Vectors of or weapons against the transmission of antibiotic resistance genes in hospital wastewater systems? - Xinyi Shuai; Zhenchao Zhou; Xiaoliang Ba; Yanhan Lin; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Guangshu Zeng; Ziye Ge; Hong Chen (Water Research, 2024)

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

A highly efficient and recyclable living biocatalyst using Shewanella@polydopamine@NH2-doped carbon dot biohybrids and polypyrrole immobilized melamine foam for microbial-photoreduction of Cr(VI) - Zheng Chen; Jian Li; Jing Zhang; Honghui Wang; Yanqiong Zeng; Feng Wang; Peng Huang; Xiaoli Chen; Liyun Ge; Randy A. Dahlgren; Hui Gao; Xiufeng Huang (Journal of Cleaner Production, 2024)

Recognizing iso-olefins as paramount intermediates for optimum isoparaffins production via CO hydrogenation - Haochen Qi; Cederick Cyril Amoo; Wuqiang Si; Jian Lou; Xuangan Liu; Chunyang Zeng; Qingjie Ge; Jian Sun; Chuang Xing; Xinhua Gao (Fuel, 2023)

Explosion behaviors of hydrogen-nitrous oxide mixtures with propane addition - Yun Ge; Hong-Hao Ma; Jia-Wei Liu; Yuan Zeng; Jun Pan; Lu-Qing Wang (Fuel, 2023)

Characterizing the impact of species/strain-specific Lactiplantibacillus plantarum with community assembly and metabolic regulation in pickled Suancai - Menglu Yang; Haimei Lai; Yali Wang; Yuan Mei; Yuli Huang; Xueqing Zeng; Lihong Ge; Jichun Zhao; Yongqing Zhu; Qiaolian Huang; Nan Zhao (Food Research International, 2023)

Illumination and reconstruction of keystone microbiota for reproduction of key flavor-active volatile compounds during paocai (a traditional fermented vegetable) fermentation - Nan Zhao; Yuli Huang; Haimei Lai; Yali Wang; Yuan Mei; Xueqing Zeng; Menglu Yang; Huajia Li; Jichun Zhao; Yongqing Zhu; Yong Zuo; Lihong Ge (Food Bioscience, 2023)

Hydrogen-rich syngas production and insight into morphology-kinetics correlation for furfural residue steam gasification in a bubbling fluidized bed - Zhenting Zha; Zefeng Ge; Yuna Ma; Mingxun Zeng; Yuqing Wu; Zenghui Hou; Fangzhou Li; Huiyan Zhang (Chemical Engineering Journal, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

A Sedentary Lifestyle Changes the Composition and Predicted Functions of the Gut Bacterial and Fungal Microbiota of Subjects from the Same Company - Longwei Xu; Wenkun Li; Lu Ling; Ziran Zhang; Zilu Cui; Jiang Ge; Yun Wang; Qianlong Meng; Yadan Wang; Kuiliang Liu; Jun Zhou; Fanxin Zeng; et al. (Current Microbiology, 2023)
A sedentary lifestyle affects the diversity and composition of the gut microbiota, but previous studies have mainly focused on bacteria instead of fungi. Here, we compared both the fecal bacterial and fungal microbiota compositions and functions in sedentary persons and controls. Subjects from the China Railway Corporation, including 99 inspectors and 88 officials, were enrolled in our study. Fecal microbiota communities were analyzed using 16S rRNA gene sequencing for bacteria and ITS sequencing for fungi. We found that the diversity of the gut microbiota of the sedentary group was significantly lower than that of the control group ( P < 0.05). The sedentary group had a higher abundance of Firmicutes, a lower abundance of Actinobacteria and Proteobacteria and a higher abundance of Ascomycota, and a lower abundance of Basidiomycota. Furthermore, functional prediction analysis of the fungal microbiota revealed more L-tryptophan degradation to 2-amino-3-carboxymuconate semialdehyde, more phospholipid remodeling (phosphatidylethanolamine, yeast), and more L-tyrosine degradation I, as well as less pentose phosphate pathway (non-oxidative branch), less adenosine nucleotide biosynthesis and less L-valine biosynthesis in the sedentary group ( P < 0.05). Thus, a sedentary lifestyle changes the composition and function of the gut microbiota. It may change the pentose phosphate pathway (non-oxidative branch), nucleic acid and amino acid biosynthesis and phospholipid metabolism in fungi.

Rapid Evaluation of Rock Mass Integrity of Engineering Slopes Using Three-Dimensional Laser Scanning - Liang Chen; Yunfeng Ge; Xuming Zeng; Haiyan Wang; Changdong Li; Shan Dong; Yang Ye; Dongming Gu (Journal of Earth Science, 2023)

Dike risk evaluation incorporating the contribution of coastal wetlands: A case study on Chongming Island, China - Wei Zhang; Jian Zeng; Zhen-Ming Ge; Peng Yun; Ke-Hua Zhu; Ke Zhou; Shi-Xian Liu; Qing Lyu; Hua-Yu Chen (Ocean & Coastal Management, 2023)

Single-use plastic bag alternatives result in higher environmental impacts: Multi-regional analysis in country with uneven waste management - Yiqi Tan; Zongguo Wen; Yupeng Hu; Xianlai Zeng; Vorada Kosajan; Ge Yin; Tingting Zhang (Waste Management, 2023)

Singlet oxygen is also involved in the formation of hypoiodous acid during the transformation of phenolic pollutants by peracetic acid in the presence of iodide - Jiamin Mai; Ge Zeng; Linqian An; Maoju Jiang; Peng Su; Qixiao Lv; Xiangyang Hou; Xiujuan Kong; Jianbo Jia; Tao Yang; Jun Ma (Chemical Engineering Journal, 2023)

Advances and Applications of Brain Organoids - Yang Li; Peng-Ming Zeng; Jian Wu; Zhen-Ge Luo (Neuroscience Bulletin, 2023)
Understanding the fundamental processes of human brain development and diseases is of great importance for our health. However, existing research models such as non-human primate and mouse models remain limited due to their developmental discrepancies compared with humans. Over the past years, an emerging model, the “brain organoid” integrated from human pluripotent stem cells, has been developed to mimic developmental processes of the human brain and disease-associated phenotypes to some extent, making it possible to better understand the complex structures and functions of the human brain. In this review, we summarize recent advances in brain organoid technologies and their applications in brain development and diseases, including neurodevelopmental, neurodegenerative, psychiatric diseases, and brain tumors. Finally, we also discuss current limitations and the potential of brain organoids.

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

Study of filtration, digestion and absorption of Chlorella pyrenoidosa by juvenile Chinese mitten crab (Eriocheir sinensis) - Jiancheng Zeng; Jian Tian; Dongqi Kan; Cui Han; Xiaoqing Fei; Xingkong Ma; Zhihong Wang; Weijian Shen; Jiaxin Yang; Jiachun Ge (Aquaculture, 2023)

A review of liquid crystal monomers: Environmental occurrence, degradation, toxicity, and human exposure of an emerging class of E-waste pollutants - Jiali Ge; Bibai Du; Mingjie Shen; Zhiqing Feng; Lixi Zeng (Environmental Pollution, 2023)

Development and testing of a planktonic index of biotic integrity (P-IBI) for Lake Fuxian, China - You Ge; Xiaohong Gu; Qingfei Zeng; Zhigang Mao; Huihui Chen; Huiting Yang (Environmental Science and Pollution Research, 2023)

A comprehensive investigation on source apportionment and multi-directional regional transport of volatile organic compounds and ozone in urban Zhengzhou - Xiaoxi Zeng; Mengjuan Han; Ge Ren; Gege Liu; Xiaoning Wang; Kailun Du; Xiaodong Zhang; Hong Lin (Chemosphere, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

3D printing MOF nanozyme hydrogel with dual enzymatic activities and visualized glucose monitoring for diabetic wound healing - Ziyan Chen; Shen Song; Huajing Zeng; Zhenlin Ge; Bin Liu; Zengjie Fan (Chemical Engineering Journal, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

Omics techniques reveal the toxicity mechanisms of three antiepileptic drugs to juvenile zebrafish (Danio rerio) brain and liver - Huiting Yang; Xiaohong Gu; Huihui Chen; Qingfei Zeng; Zhigang Mao; You Ge (Aquatic Toxicology, 2023)

Effects of Fertilization of Different Crops on Non-Point Source Pollution in the Upper Reaches of Erhai Lake Basin - Hao Zhao; Jing Li; Honggang Zheng; Jianhua Li; Jianxiong Wang; Lijun Liao; Xingyan Ge; Yunchun Chen; Xiaofei Guo; Weijun Zeng (Water, Air, & Soil Pollution, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Efficient removal of p-arsanilic acid and arsenite by Fe(II)/peracetic acid (Fe(II)/PAA) and PAA processes - Tao Yang; Linqian An; Ge Zeng; Maoju Jiang; Juan Li; Changyu Liu; Jianbo Jia; Jun Ma (Water Research, 2023)

In-situ pyrolysis kinetic analysis and fixed-bed pyrolysis behavior of ex-service wind turbine blades - Yuqing Wu; Zefeng Ge; Chen Huang; Zhenting Zha; Mingxun Zeng; Yuna Ma; Lijuan Sun; Zenghui Hou; Sheng Chu; Huiyan Zhang (Waste Management, 2023)

Gasification characteristics and synergistic effects of typical organic solid wastes under CO2/steam atmospheres - Yuna Ma; Zhenting Zha; Chen Huang; Zefeng Ge; Mingxun Zeng; Huiyan Zhang (Waste Management, 2023)

Incision history of the Mekong River valley revealed by spatially differential exhumation - Yukui Ge; Matthew Fox; Jing Liu-Zeng; Huiping Zhang; Xiaoming Shen (Geomorphology, 2023)

Protein-rich yeast extract (®fermgard) has potential antioxidant and anti-aging activities - Quancen Li; Wenwen Cai; Na Li; Weibin Su; Haicheng Li; Haibo Zhang; Zhixian Chen; Shiyu Gong; Xiaodong Ge; Bin Liu; Feng Zeng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

An ultrafast H* migration channel and oxidation activity driven by multifunctional Co atoms on twin Co0.01Mn0.29Cd0.7S homojunction surface for photocatalytic overall water splitting - Wei Tang; Tianbiao Zeng; Liguo Zhang; Baozhen Li; Ge Wang; Xueqing Xing; Yihong Ding; Changmin Hou; Wenjun Dong (Chemical Engineering Journal, 2023)

Influence of pre- or post-electron beam irradiation on heat-moisture treated maize starch for multiscale structure, physicochemical properties and digestibility - Xinyue Liu; Changyu Xi; Wei Liang; Jiayu Zheng; Wenqing Zhao; Xiangzhen Ge; Huishan Shen; Jie Zeng; Haiyan Gao; Wenhao Li (Carbohydrate Polymers, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

How does land consolidation drive rural industrial development? Qualitative and quantitative analysis of 32 land consolidation cases in China - Ge Wang; Xiaoqiu Li; Yingjie Gao; Chen Zeng; Bingkun Wang; Xiangyu Li; Xintong Li (Land Use Policy, 2023)

CALIPSO-observed Southeast Asia biomass-burning influences on aerosol vertical structure in Guangdong-Hong Kong-Macao Greater Bay Area - Xiaoyue Zeng; Siwei Li; Jia Xing; Jie Yang; Qingxin Wang; Ge Song; Mengfan Teng; Dong Zhou; Jinjun Lu (Atmospheric Research, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

How to drive strategic green innovation behavior? A qualitative comparative analysis (QCA) based on Chinese manufacturing enterprises - Jing Xiao; Ping Zeng; Ge Ren; Leimin Zhang (Environmental Science and Pollution Research, 2023)

Anthropogenic activities dominated tropical forest carbon balance in two contrary ways over the Greater Mekong Subregion in the 21st century - Baozhang Chen; Alphonse Kayiranga; Mengyu Ge; Philippe Ciais; Huifang Zhang; Andy Black; Xiangming Xiao; Wenping Yuan; Zhenzhong Zeng; Shilong Piao (Global Change Biology, 2023)
The tropical forest carbon (C) balance threatened by extensive socio‐economic development in the Greater Mekong Subregion (GMS) in Asia is a notable data gap and remains contentious. Here we generated a long‐term spatially quantified assessment of changes in forests and C stocks from 1999 to 2019 at a spatial resolution of 30 m, based on multiple streams of state‐of‐the‐art high‐resolution satellite imagery and in situ observations. Our results show that (i) about 0.54 million square kilometers (21.0% of the region) experienced forest cover transitions with a net increase in forest cover by 4.3% (0.11 million square kilometers, equivalent to 0.31 petagram of C [Pg C] stocks); (ii) forest losses mainly in Cambodia, Thailand, and in the south of Vietnam, were also counteracted by forest gains in China due mainly to afforestation; and (iii) at the national level during the study period an increase in both C stocks and C sequestration (net C gain of 0.087 Pg C) in China from new plantation, offset anthropogenetic emissions (net C loss of 0.074 Pg C) mainly in Cambodia and Thailand from deforestation. Political, social, and economic factors significantly influenced forest cover change and C sequestration in the GMS, positively in China while negatively in other countries, especially in Cambodia and Thailand. These findings have implications on national strategies for climate change mitigation and adaptation in other hotspots of tropical forests.

Intelligent detection of Multi-Class pitaya fruits in target picking row based on WGB-YOLO network - Yulong Nan; Huichun Zhang; Yong Zeng; Jiaqiang Zheng; Yufeng Ge (Computers and Electronics in Agriculture, 2023)

Detection of a mid-Holocene climate event at 7.2 ka BP based on an analysis of globally-distributed multi-proxy records - Mei Hou; Wenxiang Wu; David J. Cohen; Zhaoqi Zeng; Han Huang; Hongbo Zheng; Quansheng Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Netrin-3 Suppresses Diabetic Neuropathic Pain by Gating the Intra-epidermal Sprouting of Sensory Axons - Weiping Pan; Xueyin Huang; Zikai Yu; Qiongqiong Ding; Liping Xia; Jianfeng Hua; Bokai Gu; Qisong Xiong; Hualin Yu; Junbo Wang; Zhenzhong Xu; Linghui Zeng; et al. (Neuroscience Bulletin, 2023)

Photolysis of chlorite by solar light: An overlooked mitigation pathway for chlorite and micropollutants - Tao Yang; Mengyang Zhu; Linqian An; Ge Zeng; Chengqian Fan; Juan Li; Jin Jiang; Jun Ma (Water Research, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Faster and accurate green pepper detection using NSGA-II-based pruned YOLOv5l in the field environment - Yulong Nan; Huichun Zhang; Yong Zeng; Jiaqiang Zheng; Yufeng Ge (Computers and Electronics in Agriculture, 2023)

Decreasing summer monsoon precipitation during the Mid-Pleistocene transition revealed by a pollen record from lacustrine deposits of the Northeast Plain of China - Tao Zhan; Ye Yang; Yanxia Liang; Xiaoyan Liu; Fangming Zeng; Junyi Ge; Yongfa Ma; Keliang Zhao; Xinying Zhou; Xia Jiang; Rongfu Huang; Xun Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Catalytic fast pyrolysis of herbal medicine wastes over zeolite catalyst for aromatic hydrocarbons production - Sicheng Zhou; Shouhang Tang; Ge Li; Shanzhi Xin; Fang Huang; Xiaoye Liu; Tie Mi; Kai Huang; Lixi Zeng (Fuel, 2023)

Synergistically enhanced structural, thermal and interfacial stability of K0.45MnO2 via tailoring the local structure for high-energy and high-power potassium-ion batteries - Yan Huang; Xinyuan Zhang; Hezhe Lin; Zhixuan Wei; Yi Zeng; Xin Ge; Wei Zhang; Xiaoqi Wang; Xu Jin; Ze Xiang Shen; Fei Du (Chemical Engineering Journal, 2023)

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

Synthesis and influencing factors of high-performance concrete based on copper tailings for efficient solidification of heavy metals - Ruosong Xie; Rui Ge; Zhishuncheng Li; Guangfei Qu; Yingjie Zhang; Youxiao Xu; Yingda Zeng; Ziying Li (Journal of Environmental Management, 2023)

Field application of biodegradable microplastics has no significant effect on plant and soil health in the short term - Juncong Chu; Jie Zhou; Yue Wang; Davey L. Jones; Junyong Ge; Yadong Yang; Robert W. Brown; Huadong Zang; Zhaohai Zeng (Environmental Pollution, 2023)

Debris flow susceptibility based on the connectivity of potential material sources in the Dadu River Basin - Xinyue Liang; Yonggang Ge; Lu Zeng; Liqun Lyu; Qingmin Sun; Yuqing Sun; Xi'an Wang (Engineering Geology, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Intercropping improves soil ecosystem multifunctionality through enhanced available nutrients but depends on regional factors - Huaiying Ma; Jie Zhou; Junyong Ge; Jiangwen Nie; Jie Zhao; Zhiqiang Xue; Yuegao Hu; Yadong Yang; Leanne Peixoto; Huadong Zang; Zhaohai Zeng (Plant and Soil, 2022)

Rootstock rescues watermelon from Fusarium wilt disease by shaping protective root-associated microbiomes and metabolites in continuous cropping soils - An-Hui Ge; Zhi-Huai Liang; Li-Li Han; Ji-Ling Xiao; Yi Zhang; Qing Zeng; Ji-Fang Xiang; Chao Xiong; Li-Mei Zhang (Plant and Soil, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Inhibition of AoAur1 increases mycelial growth, hyphal fusion and improves physiological adaptation to high-temperature stress in Aspergillus oryzae - Jinxin Ge; Zhe Zhang; Yuan Li; Zhihong Hu; Bin He; Yongkai Li; Bin Zeng; Chunmiao Jiang (Archives of Microbiology, 2022)

Characterization and mutagenesis of a novel Mycobacterium smegmatis-derived glutamate decarboxylase active at neutral pH - Yudi Li; Guiying Chen; Fanglan Ge; Ting Dang; Yao Ren; Bei Zeng; Wei Li (World Journal of Microbiology and Biotechnology, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Numerical Investigation on the Effect of Asymmetry of Flow Velocity on the Wake Vortex of Hydrofoils - Xiang Xia; Liangcheng Ge; Lingjiu Zhou; Yingyao Feng; Haiyan Zeng; Zhengwei Wang (Journal of Marine Science and Engineering, 2022)
The Karman vortex street is a common flow phenomenon. In hydraulic machinery, it is usually located downstream of the guide vanes and the runner blades, which reduces hydraulic performance and may also cause fatigue damage to the structure. The latest research suggested that the difference in velocity gradient on each side of the blade trailing edge may have a significant impact on the strength of the wake vortex. The current work aims to verify the above conclusion and further explore the influence of asymmetry of flow velocity on the wake vortex. A numerical model with the velocity ratio, α, between the two sides of the hydrofoil as the only variable was designed, and the wake characteristics were solved by a computational fluid dynamics (CFD) method based on the finite volume. The unsteady Reynolds-average Navier–Stokes (URANS) equations were numerically solved by coupling with a transitional shear-stress transport (SST) turbulence model. The results showed that with the increase of α, the vortex shedding frequency decreased first, and then increased after reaching the critical velocity ratio αc1 ≈ 1.4. The vortex intensity first gradually decreased, and the vortex street suddenly disappeared after reaching the critical velocity ratio αc2 ≈ 2.2. The value of αc1 was affected by the thickness of the trailing edge, and αc2 was affected by the thickness and the Reynolds number. Besides, the asymmetry of the flow velocity also affected the effectiveness of the trailing-edge trimming. This research can provide references for the design of hydraulic machinery and other submerged structures.

HSV-1 H129-Derived Anterograde Neural Circuit Tracers: Improvements, Production, and Applications - Hong Yang; Feng Xiong; Yi-Ge Song; Hai-Fei Jiang; Hai-Bin Qin; Jing Zhou; Sha Lu; Steven F. Grieco; Xiangmin Xu; Wen-Bo Zeng; Fei Zhao; Min-Hua Luo (Neuroscience Bulletin, 2021)

Integrated mRNA and microRNA Transcriptome Sequencing Characterizes Sequence Variants and mRNA-microRNA Regulatory Networks in Grass Carp Fibroblasts Infected with Virulent and Attenuated GCRV - Qiucheng Yao; Mengdi Zhang; Shaopo Zu; Hong Yang; Weitian Xie; Jinjun Chen; Zhibao Chen; Ye Ge; Weiwei Zeng; Zhihui Zhao (Marine Biotechnology, 2021)

Post-Orogenic Tectonic Evolution of the Jiangnan-Xuefeng Orogenic Belt: Insights from Multiple Geochronometric Dating of the Mufushan Massif, South China - Chuanbo Shen; Di Hu; Kyoungwon Min; Chaoqun Yang; Xiaowei Zeng; Hongyang Fu; Xiang Ge (Journal of Earth Science, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Spatio-temporal variation in rock exhumation linked to large-scale shear zones in the southeastern Tibetan Plateau - Yukui Ge; Jing Liu-Zeng; Jinyu Zhang; Wei Wang; Yuntao Tian; Matthew Fox; Lingsen Zeng; Xiaoming Shen; Heng Wang; Ze Su; Kejia Xie (Science China Earth Sciences, 2020)

Fractal dimension analysis for seismicity spatial and temporal distribution in the circum-Pacific seismic belt - Lirong Yin; Xiaolu Li; Wenfeng Zheng; Zhengtong Yin; Lihong Song; Lijun Ge; Qingchuan Zeng (Journal of Earth System Science, 2019)

Evaluation of vulnerable PM2.5-exposure individuals: a repeated-measure study in an elderly population - Haiyan Chu; Junyi Xin; Qi Yuan; Xu Zhang; Wang Pan; Xinying Zeng; Yaoyao Chen; Gaoxiang Ma; Yuqiu Ge; Mulong Du; Na Tong; Xiaobo Li; et al. (Environmental Science and Pollution Research, 2018)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Relationships between soil–litter interface enzyme activities and decomposition in Pinus massoniana plantations in China - Xiaogai Ge; Wenfa Xiao; Lixiong Zeng; Zhilin Huang; Benzhi Zhou; Marcus Schaub; Mai-He Li (Journal of Soils and Sediments, 2017)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Catastrophic debris flows on July 10th 2013 along the Min River in areas seriously-hit by the Wenchuan earthquake - Yong-gang Ge; Peng Cui; Jian-qiang Zhang; Chao Zeng; Feng-huan Su (Journal of Mountain Science, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

Ginkgo biloba extract reducing myocardium cells apoptosis by regulating apoptotic related proteins expression in myocardium tissues - Zeng Yong Qiao; Jian Hua Huang; Jiang Wei Ma; Ya Wei Xu; Jun Xie; Hua Jin Liu; San Jun Xiong; Guang Hao Ge (Molecular Biology Reports, 2014)

Geochronology and petrogenesis of Cretaceous A-type granites from the NE Jiangnan Orogen, SE China - Jie Zhou; Yao-Hui Jiang; Guangfu Xing; Yong Zeng; Weiya Ge (International Geology Review, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein - Ren-Jie Zhou; Xue-Qin Yang; Dong Wang; Qian Zhou; Lei Xia; Meng-Xia Li; Lin-Li Zeng; Ge Wang; Zhen-Zhou Yang (Cell Biochemistry and Biophysics, 2012)

Analysis of the External Pressure on Casings Induced by Salt-Gypsum Creep in Build-up Sections for Horizontal Wells - Weifeng Ge; Mian Chen; Yan Jin; Fuxiang Zhang; Yunhu Lu; Pei Yang; Jihui Ding; Hao Zeng (Rock Mechanics and Rock Engineering, 2011)

Downregulation of Cinnamyl Alcohol Dehydrogenase (CAD) Leads to Improved Saccharification Efficiency in Switchgrass - Chunxiang Fu; Xirong Xiao; Yajun Xi; Yaxin Ge; Fang Chen; Joseph Bouton; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2011)

Efficient biotransformation of cholesterol to androsta-1,4-diene-3,17-dione by a newly isolated actinomycete Gordonia neofelifaecis - Yuchang Liu; Guiying Chen; Fanglan Ge; Wei Li; Lihua Zeng; Weiguo Cao (World Journal of Microbiology and Biotechnology, 2011)

Thick Miocene eolian deposits on the Huajialing Mountains: The geomorphic evolution of the western Loess Plateau - Tao Zhan; ZhengTang Guo; HaiBin Wu; JunYi Ge; Xin Zhou; ChunLin Wu; FangMing Zeng (Science China Earth Sciences, 2011)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

In vitro synergistic activity between 8-methoxypsoralen and ethambutol, isoniazid, and rifampin when used in combination against Mycobacterium tuberculosis - Fa Ge; Fanli Zeng; Na Guo; Junwen Fan; Yu Song; Siguo Liu; Xiuping Wu; Xuelin Wang; Xuming Deng; Qi Jin; Lu Yu (World Journal of Microbiology and Biotechnology, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Agrobacterium-Mediated Transformation of Switchgrass and Inheritance of the Transgenes - Yajun Xi; Chunxiang Fu; Yaxin Ge; Rangaraj Nandakumar; Hiroshi Hisano; Joseph Bouton; Zeng-Yu Wang (BioEnergy Research, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Effect of needle damage on the release rate of Masson pine (Pinus massoniana) volatiles - Jian-Wei Su; Ju-Ping Zeng; Xiao-Wei Qin; Feng Ge (Journal of Plant Research, 2009)

Isolation and identification of hydroxythiohomosildenafil in herbal dietary supplements sold as sexual performance enhancement products - L. Li; M.-Y. Low; F. Aliwarga; J. Teo; X.-W. Ge; Y. Zeng; B.C. Bloodworth; H.-L. Koh (Food Additives & Contaminants: Part A, 2009)

Generation of transgenic Lolium temulentum plants by Agrobacterium tumefaciens-mediated transformation - Yaxin Ge; Xiaofei Cheng; Andrew Hopkins; Zeng-Yu Wang (Plant Cell Reports, 2007)

Transgenic zoysiagrass (Zoysia japonica) plants obtained by Agrobacterium-mediated transformation - Yaxin Ge; Tina Norton; Zeng-Yu Wang (Plant Cell Reports, 2006)

Recent advances in genetic transformation of forage and turf grasses - Zeng-Yu Wang; Yaxin Ge (In Vitro Cellular & Developmental Biology - Plant, 2006)